1991
DOI: 10.1007/bf01311299
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lethal and persistent rat parvovirus infection by antibody

Abstract: Two day-old athymic (rnu/rnu) and euthymic (rnu/+) rat pups nursing immune or non-immune dams were inoculated oronasally with the Yale strain of rat virus (RV-Y). All athymic and euthymic pups (57/57) from immune dams remained clinically normal, whereas 51 of 66 athymic and euthymic pups from non-immune dams died within 30 days. Infectious RV was detected by explant culture in 12 of 15 surviving pups of both genotypes from non-immune dams 30 days after inoculation, but in none of the 57 surviving pups from imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The variability with which RV was recovered, especially at long intervals after inoculation of pups, coupled with the detection only of 1.3 and 0.8 kbp DNA bands in these seropositive rats, is consistent with potential restriction of RV expression by antibody. In addition, persistently infected athymic pups, which make little or no antibody to RV, harbor RV DNA typical of RF virus rather than DNA bands observed in persistently infected, seropositive euthymic pups [15].…”
Section: Discussionmentioning
confidence: 92%
“…The variability with which RV was recovered, especially at long intervals after inoculation of pups, coupled with the detection only of 1.3 and 0.8 kbp DNA bands in these seropositive rats, is consistent with potential restriction of RV expression by antibody. In addition, persistently infected athymic pups, which make little or no antibody to RV, harbor RV DNA typical of RF virus rather than DNA bands observed in persistently infected, seropositive euthymic pups [15].…”
Section: Discussionmentioning
confidence: 92%
“…By contrast, Virelizier (51) and subsequently ourselves (41) found that antibody treatment could cure influenza virus pneumonia in immunodeficient mice. Antibody treatments have reportedly also cured other viral diseases in immunodeficient mice, such as Sindbis virus infection of the central nervous system in severe combined immunodeficiency (SCID) mice (33), Theiler's murine encephalomyelitis virus infection in athymic mice (15), and parvovirus infection in athymic newborn rats (17). In addition, treatment with a singularly effective monoclonal antibody (MAb) but not with an antiserum cured a herpes simplex virus infection of the vaginal mucous membranes in Tcell-depleted mice (14), although passive antibody often only delayed morbidity in this infection (28,37,47,55).…”
mentioning
confidence: 99%
“…Additionally, transfer of colostral or serum antibodies before or at the time of infection protected infant rats from developing RV infection. In contrast, administration of immune sera to infant rats 1 day after virus inoculation failed to prevent RV infection (11). Furthermore, rats inoculated at 6 days of age develop high anti-RV antibody titers, and yet virus is able to persist (15).…”
mentioning
confidence: 93%